The role of gastrointestinal hormones in the pathogenesis of obesity and type 2 diabetes - Adamska, Edyta; Ostrowska, Lucyna; Górska, Maria; Krętowski, Adam (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Obesity, influencing the increase of incidence of type 2 diabetes, cardiovascular complications and cancer is a growing medical problem worldwide. The feelings of hunger and satiety are stimulated by the “gut-brain axis”, where a crucial role is played by gastrointestinal hormones: glucagon-like peptide 1, glucose-dependent insulinotropic polypeptide, pancreatic polypeptide, peptide YY, oxyntomodulin, cholecystokinin and ghrelin. These hormones affect not only the functioning of the digestive tract, but also might have effects on insulin secretion and are mediators which affect brain areas involved in the regulation of food intake. The effect of their actions can be antagonistic as well as an additive or synergistic, and their secretion is dependent on many factors, such as dietary nutrients or the energy state of the body. Changes in circulating gut hormones concentrations result in activation of various pathways primarily within the hypothalamus and brain stem areas, which modulate feeding behaviour and a number of metabolic processes.